2018
DOI: 10.1038/s41598-018-22635-9
|View full text |Cite
|
Sign up to set email alerts
|

HSP27 inhibitor attenuates radiation-induced pulmonary inflammation

Abstract: Radiation therapy has been used to treat over 70% of thoracic cancer; however, the method usually causes radiation pneumonitis. In the current study, we investigated the radioprotective effects of HSP27 inhibitor (J2) on radiation-induced lung inflammation in comparison to amifostine. In gross and histological findings, J2 treatment significantly inhibited immune cell infiltration in lung tissue, revealing anti-inflammatory potential of J2. Normal lung volume, evaluated by micro-CT analysis, in J2-treated mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…To mimic the effects of clinical radiotherapy in an animal model of IR-induced lung damage, we had previously exposed mice lungs to high-dose radiation using a small-animal micro-irradiator (X-RAD320) equipped with a collimator system (to produce focal radiation beams) 7,8,28 . These studies showed that radiation pneumonitis occurs in mice within 2 weeks of exposure to 60-100 Gy of IR 8,15,28 . Herein, we evaluated the effects of LXA 4 on pneumonitis 2 weeks after 75 Gy IR by evaluating the lung morphology and performing hematoxylin and eosin (H&E) staining and pulmonary function assays (micro-computed tomography (CT) and flexiVent TM ).…”
Section: Lxa 4 Inhibits Radiation-induced Lung Inflammatory Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…To mimic the effects of clinical radiotherapy in an animal model of IR-induced lung damage, we had previously exposed mice lungs to high-dose radiation using a small-animal micro-irradiator (X-RAD320) equipped with a collimator system (to produce focal radiation beams) 7,8,28 . These studies showed that radiation pneumonitis occurs in mice within 2 weeks of exposure to 60-100 Gy of IR 8,15,28 . Herein, we evaluated the effects of LXA 4 on pneumonitis 2 weeks after 75 Gy IR by evaluating the lung morphology and performing hematoxylin and eosin (H&E) staining and pulmonary function assays (micro-computed tomography (CT) and flexiVent TM ).…”
Section: Lxa 4 Inhibits Radiation-induced Lung Inflammatory Responsesmentioning
confidence: 99%
“…1c). Microcomputed tomographic (micro-CT) images taken 2 weeks after IR show that pulmonary consolidation throughout the left lung of irradiated mice makes it possible to measure high air-tissue contrast 8,28 . We found that LXA 4 reduced IR-induced pulmonary consolidation ( Fig.…”
Section: Lxa 4 Inhibits Radiation-induced Lung Inflammatory Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…HSP27 can also mediate the effects of certain therapeutic approaches. RT increased levels of HSP27 and p-HSP27 in head and neck cancer cell lines [28], and in mouse lung in vivo [29]. Pavan and colleagues [30] found that HSP27 was required for spontaneous lung metastasis in a mouse model of ovarian cancer and inhibition of HSP27 has been shown to sensitize tumors to chemotherapy [30] and RT [31].…”
Section: Introductionmentioning
confidence: 99%
“…Quantification was performed by comparative CT method (∆∆CT). Extracted 30 μg proteins were separated by SDS-PAGE, the membranes were probed with primary antibody (1:1000), followed by incubation with horseradish peroxidase-coupled secondary antibody 45 . Detection was performed with a chemiluminescence-based detection kit (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%